Pengendalian Banjir di Daerah Aliran Sungai (DAS) Ampal Kota Balikpapan: Analisa Kapasitas Sungai - Rossana Margaret Kadar Yanti; Andika Ade Indra Saputra (Jurnal Aplikasi Teknik Sipil, 2021)
Ampal acts as the main channel in ampal drainage system. This river is located inurban areas that serves to drain the water from the upstream to the sea (MakassarStrait). Channel reduction, occurred in the middle to downstream channel, caused bysedimentation leads to capacity reduction, further its unability to drain the flood. Thepurpose of this study is to determine the river capacity as an alternative floodprevention. Hydrology and hydraulics data are used in the analysis process. In flooddischarge calculation, the SCS-CN (Soil Conservation Service - curve number) runoffcalculation method is used. Based on the data and analysis, the maximum flooddischarge values flowing in the Ampal catchment are 100.20 m3/s for the middlesection and 170.40 m3/s at the downstream. The central part of the Ampal Rivercapacity is 60.69 m3/sec. and 168.50 m3/sec. at the downstream. Using three additional bozem, the problem at Section 3 Ampal River can be solved, with 7.70 m3/s flood discharge reduction.